Bauman, Elias and Latour on modernity and its alternatives : three contemporary sociological theorists on modernity and other options - Segre, Sandro (Anthem Press, 2020)
'Bauman, Elias and Latour on Modernity and Its Alternatives' summarizes and compares the sociological works of three contemporary authors insofar as they deal with the themes of modernity and its alternatives. These alternatives are either deemed to be possible or actually experienced, whether historically or in the present.